Composite positive electrode material and preparation method thereof, positive plate and secondary battery
By introducing metal cations into the ternary positive electrode material and covering metal nitride, the problems of low compaction density and poor pressure resistance are solved, and higher energy density and cycle life are achieved.
Patent Information
- Application Number
- CN202411890565.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing ternary cathode materials have low compaction density and poor pressure resistance, making it difficult to meet the needs of improving the energy density and cycle life of lithium batteries.
Using composite positive electrode material, the particle strength and pressure resistance of the material are improved by introducing metal cations into the core material and covering metal nitrides on the shell layer.
The compaction density and voltage resistance of composite positive electrode materials are significantly improved, the structural stability and electrochemical properties of the positive electrode materials are enhanced, and the energy density and cycle life of lithium batteries are improved.
Smart Images

Figure CN119833596A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] Since its commercialization in the 1990s, lithium batteries have been widely used because of their high energy density, high charge and discharge efficiency, low self-discharge, long service life and environmental friendliness. At present, they have been applied to consumer electronics, aerospace, military, power tools and electric vehicles. With the development of technology, people have higher and higher requirements for the endurance of lithium-ion batteries in both the consumer field and the power battery field. The development of high energy density has become the key to the development of lithium batteries. Generally, it can be started from two aspects. One is to develop new high-gram capacity positive and negative electrode materials; the other is to increase the charge and discharge voltage of lithium batteries. Increasing the charge and discharge voltage of lithium batteries can simultaneously increase the mass energy density and volume energy density of lithium batteries, and can also reduce the cost of lithium batteries, which has become a hot topic of research.
[0003] There is an increasing demand for improving the energy density of ternary positive electrode materials. Increasing the voltage upper limit to improve the energy density of ternary positive electrode materials will easily lead to a decrease in the electrical performance of the ternary positive electrode materials. It is necessary to simultaneously improve the compaction density and pressure resistance of the ternary positive electrode material powder to improve the energy density of the ternary positive electrode materials.
[0004] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0005] One of the purposes of the present invention is to provide a composite positive electrode material to address the deficiencies of the prior art, so as to improve the problems of low compaction density and poor pressure resistance of the current ternary positive electrode materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A composite positive electrode material, comprising an outer shell layer and an inner core material, wherein the outer shell layer comprises a metal nitride; wherein the chemical formula of the inner core material is LiNi x Co y Mn 1-x-y-z Me z O2, 0≤x≤1, 0≤y≤1, 0≤z≤0.2, and x+y+z>0; the chemical formula of the metal nitride is Me p N q , 1≤p≤3, 1≤q≤3; wherein Me includes at least one of Mn, Co, Ni, Fe, Al, Cu, Ti, Cr, Zr, Zn, Mg and W.
[0008] Preferably, the mass ratio of the outer shell layer and the inner core material is (0.1-0.3):100.
[0009] Preferably, the composite positive electrode material comprises secondary particles composed of a plurality of primary particles, the primary particles are polycrystalline particles, and the ratio of the particle size D50 of the primary particles to the particle size D50 of the secondary particles is 1:(5-40).
[0010] Preferably, the particle size D50 of the secondary particles is 8 to 40 μm; and the particle size D50 of the primary particles is 0.8 to 2.0 μm.
[0011] The second object of the present invention is to provide a method for preparing a composite positive electrode material, comprising the following steps:
[0012] S1, after the lithium compound, the nickel-cobalt-manganese ternary precursor and the metal nitride are uniformly mixed, the first stage of sintering is performed under a protective atmosphere, and then the temperature is continuously raised to perform the second stage of sintering, and then the temperature is kept, and after cooling, the mixture is ground in an inert atmosphere to obtain a pre-sintered product;
[0013] S2. Add metal nitride to the pre-sintered product, and then fully mix it, perform the first stage of sintering under a protective atmosphere, continue to increase the temperature to perform the second stage of sintering, then keep the temperature, grind it in an inert atmosphere after cooling, and finally obtain a composite positive electrode material.
[0014] Preferably, in step S1, the molar ratio of the lithium compound, the nickel-cobalt-manganese ternary precursor, and the metal nitride is Li:(Ni+Co+Mn):Me=(1.01-1.10):1:(0.005-0.3).
[0015] Preferably, in step S1, the first stage sintering temperature is 800-1400°C, the heating rate is 1-5°C / min, and the sintering time is 2-10h;
[0016] The second stage sintering temperature is 1200-1800°C, the heating rate is 5-10°C / min, the sintering time is 1-8h, and the insulation temperature is 400-1000°C.
[0017] Preferably, in step S2, the first stage sintering temperature is 600-1200°C, the heating rate is 1-5°C / min, and the sintering time is 4-14h;
[0018] The second stage sintering temperature is 1000-1600° C., the heating rate is 5-10° C. / min, the sintering time is 1-8 hours, and the holding temperature is 200-800° C. The third object of the present invention is to provide a positive electrode sheet, comprising the positive electrode material described above.
[0019] A fourth object of the present invention is to provide a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: the composite positive electrode material provided by the present invention, by doping the core material with metal cations and coating it with metal nitrides, the metal nitride outer shell layer can effectively isolate the direct contact between the positive electrode material and the electrolyte, reduce the occurrence of side reactions, thereby improving the chemical stability and cycle stability of the material, and improving the pressure resistance of the material. Introducing an appropriate amount of metal cations into the core ternary material can change the crystal structure and electronic structure of the material, thereby improving its structural stability and electrochemical performance. Under the synergistic effect of the two, the particle strength of the composite positive electrode material is significantly improved, and the compaction density and pressure resistance are also improved. This not only enhances the structural stability of the positive electrode material, but also helps to improve the energy density and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of a composite positive electrode material prepared according to an embodiment of the present invention. DETAILED DESCRIPTION
[0022] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0023] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0024] In a first aspect of the present invention, a composite positive electrode material is provided, comprising an outer shell layer and an inner core material, wherein the outer shell layer comprises a metal nitride; wherein the chemical formula of the inner core material is LiNi x Co y Mn 1-x-y-z Me z O2, 0≤x≤1, 0≤y≤1, 0≤z≤0.2, and x+y+z>0; the chemical formula of the metal nitride is Me p N q , 1≤p≤3, 1≤q≤3; wherein Me includes at least one of Mn, Co, Ni, Fe, Al, Cu, Ti, Cr, Zr, Zn, Mg and W.
[0025] The core material is coated with a metal nitride in the outer shell layer, which can increase the particle size and primary particle size of the core material, thereby improving the compaction density and pressure resistance of the material. Preferably, the metal nitride is preferably zirconium nitride, which has high hardness and good wear resistance, and thus can improve the compaction density and pressure resistance of the composite positive electrode material; at the same time, the structure of zirconium nitride is stable, and changes little during the battery charging and discharging process, which can improve the cycle life of the battery; zirconium nitride as an outer shell layer also has good electronic conductivity and electrochemical activity, which can effectively improve the battery's charge and discharge efficiency and cycle stability.
[0026] In some embodiments, the mass ratio of the outer shell layer to the core material is (0.1-0.3):100. Specifically, it may be 0.1:100, 0.2:100, 0.3:100, and may include but are not limited to the values listed above; the mass ratio within the above range can optimize the particle size and compaction density of the prepared composite positive electrode material.
[0027] In some embodiments, the composite positive electrode material includes secondary particles composed of a plurality of primary particles, the primary particles are polycrystalline particles, and the ratio of the average particle size of the primary particles to the average particle size of the secondary particles is 1:5 to 40. Among them, the primary particles have a higher energy density, a large specific surface area, multiple lithium ion migration channels, and a short path, so the rate performance is good; the secondary particles composed of primary particles can take into account the advantages of large particles and small particles, can improve the cycle performance and compaction density of the primary particles, and make up for the safety of the primary particles.
[0028] Among them, the ratio of the particle size D50 of the primary particles to the particle size D50 of the secondary particles can be 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, which may include but are not limited to the values listed above.
[0029] In some embodiments, the particle size D50 of the secondary particles is 8-40 μm; the particle size D50 of the primary particles is 0.8-2.0 μm. The particle size D50 of the secondary particles can be 8 μm, 9 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, including but not limited to the values listed above; the particle size D50 of the primary particles can be 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, including but not limited to the values listed above.
[0030] A second aspect of the present invention provides a method for preparing the composite positive electrode material, comprising the following steps:
[0031] S1, after the lithium compound, the nickel-cobalt-manganese ternary precursor and the metal nitride are uniformly mixed, the first stage of sintering is performed under a protective atmosphere, and then the temperature is continuously raised to perform the second stage of sintering, and then the temperature is kept, and after cooling, the mixture is ground in an inert atmosphere to obtain a pre-sintered product;
[0032] S2. Add metal nitride to the pre-sintered product, and then fully mix it, perform the first stage of sintering under a protective atmosphere, continue to increase the temperature to perform the second stage of sintering, then keep the temperature, grind it in an inert atmosphere after cooling, and finally obtain a composite positive electrode material.
[0033] In an embodiment of the present invention, in step S1, the molar ratio of the lithium compound, the nickel-cobalt-manganese ternary precursor, and the metal nitride is Li:(Ni+Co+Mn):Me=(1.01-1.10):1:(0.005-0.3), preferably Li:(Ni+Co+Mn):Me=1.05:1:(0.01-0.2). Specifically, it may be 1.05:1:0.01, 1.05:1:0.01, 1.05:1:0.02, 1.05:1:0.03, 1.05:1:0.04, 1.05:1:0.05, 1.05:1:0.06, 1.05:1:0.07, 1.05:1:0.08, 1.05:1:0.09, 1.05:1:0.1, 1.05:1:0.15, 1.05:1:0.2, and may include but are not limited to the values listed above, and 1.05:1:0.1 is more preferred.
[0034] In an embodiment of the present invention, in step S1, the sintering temperature of the first stage is 800-1400°C, preferably 1000-1200°C; the heating rate is 1-5°C / min, and the sintering time is 2-10h, preferably 4-8h; the sintering temperature of the second stage is 1200-1800°C, preferably 1400-1600°C; the heating rate is 5-10°C / min, and the sintering time is 1-8h, preferably 2-6h; the insulation temperature is 400-1000°C, preferably 600-800°C.
[0035] In the embodiment of the present invention, in step S2, the first stage sintering temperature is 600-1200°C, preferably 800-1000°C; the heating rate is 1-5°C / min, and the sintering time is 4-14h, preferably 6-12h.
[0036] The second stage sintering temperature is 1000-1600°C, preferably 1200-1400°C; the heating rate is 5-10°C / min, the sintering time is 1-8h, preferably 1-5h; the insulation temperature is 200-800°C, preferably 400-600°C.
[0037] The present invention adopts multiple staged sintering and uses nitride to coat the material, which can improve the stability of the surface morphology of the core material, i.e., the ternary material, and obtain a denser coating layer, and can increase the particle size of the ternary positive electrode material particles and the particle size of its primary particles. At the same time, the present invention improves the morphological stability and density of the ternary material surface by controlling the temperature and time.
[0038] Among them, in step S1, the lithium compound can be at least one of lithium sulfate, lithium nitrate, lithium chloride, and lithium carbonate, preferably lithium carbonate; the metal nitride can be at least one of cobalt nitride, iron nitride, aluminum nitride, copper nitride, titanium nitride, zinc nitride, zirconium nitride, and magnesium nitride, preferably zirconium nitride.
[0039] Compared with traditional single positive electrode active materials, the composite positive electrode material in the present application can improve the particle strength of the composite positive electrode material, improve the compaction density and pressure resistance of the material, and thus improve the energy density of the positive electrode material by doping the core material with metal cations and coating the outer surface of the core material with nitrides.
[0040] 2. Positive electrode
[0041] The third aspect of the present invention provides a positive electrode sheet, comprising the composite positive electrode material described above, specifically comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, and the positive electrode active material is the positive electrode material described in the present invention.
[0042] The positive electrode current collector can be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to aluminum foil.
[0043] 3. Secondary battery
[0044] A fourth aspect of the present invention is to provide a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.
[0045] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials in the art that are suitable for use as a negative electrode current collector for lithium-ion batteries. For example, the negative electrode current collector can be, but is not limited to, metal foil, and more specifically, can be, but is not limited to, copper foil.
[0046] The separator can be any material suitable for lithium-ion battery separators in the art, for example, it can be a combination of one or more materials including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0047] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.
[0048] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0049] Example 1
[0050] The preparation method of the composite positive electrode material in this embodiment is:
[0051] S1: After lithium carbonate, nickel-cobalt-manganese ternary precursor and zirconium nitride are fully mixed in a stoichiometric ratio of Li:(Ni+Co+Mn):Zr=1.05:1:0.1, the mixture is heated to 1100°C at a heating rate of 1-5°C / min in a nitrogen atmosphere and sintered for 6 hours, then the mixture is heated to 1500°C at a heating rate of 5-10°C / min and sintered for 4 hours, then kept at 700°C for 8 hours, cooled, and ground in a nitrogen atmosphere until there is no obvious granularity to obtain a pre-sintered product.
[0052] S2: Add zirconium nitride to the pre-sintered product, and then mix it thoroughly by ball milling. Then, heat it to 900°C at a heating rate of 1 to 5°C / min in a nitrogen atmosphere and sinter it for 8 hours. Then continue to heat it to 1300°C at a heating rate of 5 to 10°C / min and calcine it for 3 hours. Then, keep it at 500°C for 3 hours. After cooling, grind it in a nitrogen atmosphere to finally obtain a nitride-modified nickel-cobalt-manganese-oxide lithium ternary composite positive electrode material.
[0053] Embodiment 2-3
[0054] The difference between this embodiment and embodiment 1 is that in step S1, the stoichiometric ratio of zirconium nitride is shown in Table 1 for details.
[0055] The rest is the same as in Example 1 and will not be described again here.
[0056] Embodiment 4-5
[0057] The difference between this embodiment and embodiment 1 is the sintering temperature of step S1; see Table 1 for details.
[0058] The rest is the same as in Example 1 and will not be described again here.
[0059] Embodiment 6-7
[0060] The difference between this embodiment and embodiment 1 is the sintering time of step S1; see Table 1 for details.
[0061] The rest is the same as in Example 1 and will not be described again here.
[0062] Embodiments 8 to 9
[0063] The difference between this embodiment and embodiment 1 is that zirconium nitride of different mass ratios is added in step S2, so that the mass ratios of the outer shell layer and the inner core material are different; see Table 2 for details.
[0064] The rest is the same as in Example 1 and will not be described again here.
[0065] Embodiments 10 to 11
[0066] The difference between this embodiment and embodiment 1 is the sintering temperature of step S2; see Table 2 for details.
[0067] The rest is the same as in Example 1 and will not be described again here.
[0068] Embodiments 12 to 13
[0069] The difference between this embodiment and embodiment 1 is the sintering time of step S2; see Table 2 for details.
[0070] The rest is the same as in Example 1 and will not be described again here.
[0071] Comparative Example 1
[0072] The lithium carbonate and nickel-cobalt-manganese ternary precursors are fully mixed in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.05:1, heated to 1100°C at a heating rate of 1-5°C / min in a nitrogen atmosphere, sintered for 6h, kept at 700°C for 8h, cooled and ground in a nitrogen atmosphere to obtain a once-sintered ternary material.
[0073] Comparative Example 2
[0074] The difference between this comparative example and comparative example 1 is that the product of the primary sintering is subjected to secondary calcination, as shown in Tables 1 and 2 for details.
[0075] The rest is the same as Comparative Example 1 and will not be described again.
[0076] Comparative Example 3
[0077] The difference between this comparative example and Example 1 is that there is no step S2.
[0078] The rest is the same as in Example 1 and will not be described again here.
[0079] Comparative Example 4
[0080] The difference between this comparative example and Example 1 is that there is no second stage of temperature rise sintering in step S1.
[0081] The rest is the same as in Example 1 and will not be described again here.
[0082] Comparative Example 5
[0083] The difference between this comparative example and Example 1 is that there is no second stage of temperature rise sintering in step S2.
[0084] The rest is the same as in Example 1 and will not be described again here.
[0085] Comparative Example 6
[0086] The difference between this comparative example and Example 1 is that zirconium nitride is not added in step S1.
[0087] The rest is the same as in Example 1 and will not be described again here.
[0088] Comparative Example 7
[0089] The difference between this comparative example and Example 1 is that zirconium nitride is not added in step S2.
[0090] The rest is the same as in Example 1 and will not be described again here.
[0091] The specific preparation parameters are summarized in Tables 1 and 2.
[0092] Table 1
[0093]
[0094]
[0095] Table 2
[0096]
[0097] The ternary materials prepared in Examples 1-13 and the composite positive electrode materials prepared in Comparative Examples 1-7 were assembled into lithium-ion button cells, and the electrical performance was tested at room temperature, with a charge and discharge condition of 0.5C and a charge and discharge range of 3.0V-4.5V. The electrical performance test results are as follows:
[0098] Table 3
[0099]
[0100] Particle size measurement method: Add the weighed ternary cathode material into the particle size analyzer. The dispersant in the instrument is pure water. The speed of the agitator is 3000rpm. By adjusting the refractive index, the test cycle is repeated 3 times, and finally the particle size data of the particle size analyzer is read.
[0101] Table 4 Test results of secondary particle size and primary particle size
[0102]
[0103] Compacted density measurement method: Load the weighed ternary cathode material into the measuring cylinder of the compaction device, and fix the measuring cylinder on the support. Turn the cam, and the directional rod drives the support to slide up and down, and press it onto the anvil, and then pressurize it at a pressure of 1 t per minute, and finally pressurize it to 5 t. Measure the volume of the ternary cathode material in the measuring cylinder, and the ratio of the mass of the ternary cathode material to the volume is the compacted density of the ternary cathode material.
[0104] Table 5 Compacted density test results
[0105]
[0106]
[0107] It can be seen from the above test results that Examples 1 to 3 and Comparative Examples 1 to 2 illustrate that the doping of metal elements in the core material in step S1, combined with multiple staged sintering; the use of 0.1-0.3wt% nitride coating in step S2, combined with multiple staged sintering and controlling the sintering temperature and time, are beneficial to improving the comprehensive electrical properties of the modified nickel-cobalt-lithium-manganese oxide ternary material.
[0108] From Examples 1 to 3 and Comparative Examples 1 and 2, in Examples 1 to 3, when the mass ratio of the nitride added in the sintering step S1 is 0.01-0.2, the particle size, primary particle size and compaction density are all greater than those of the comparative example, and the mass ratio of the added nitride is optimal when it is 0.1; From Examples 1, 4, 5 and Comparative Examples 1 and 2, by changing the sintering temperature, the particle size, primary particle size and compaction density of the prepared composite positive electrode material are all greater than those of the comparative example, wherein the particle size and primary particle size increase with increasing temperature, but the compaction density is better when the first stage sintering temperature, the second stage sintering temperature and the insulation temperature are 1100°C, 1500°C and 700°C, respectively.
[0109] From the perspective of Examples 1, 6, and 7 compared with Comparative Examples 1 and 2, when the first sintering time, the second sintering time, and the holding time of the first sintering are 4 to 8 hours, 2 to 6 hours, and 6 to 10 hours, respectively, the particle size, the primary particle size, and the compacted density are all greater than those of the comparative example, wherein the particle size increases with time, but the primary particle size and the compacted density are optimal when the first sintering time, the second sintering time, and the holding time are 6 hours, 4 hours, and 8 hours, respectively; From the perspective of Examples 1, 8, and 9 compared with Comparative Examples 1 and 2, in Examples 1, 8, and 9, when the mass ratio of the nitride coating layer is 0.1%-0.3%, the particle size, the primary particle size, and the compacted density are all greater than those of the comparative example, wherein the particle size, the primary particle size, and the compacted density increase with the increase of the mass ratio of the added nitride; From Example 1, Comparative Examples 4 to 5 and Comparative Examples 1 to 3, when the second sintering in step S1 or the second sintering in step S2 is cancelled, the particle size, primary particle size and compaction density are all greater than those of Comparative Examples 1 and 2, but the particle size and compaction density of Comparative Example 4 are smaller than those of Comparative Example 3, and the particle size, primary particle size and compaction density of Comparative Examples 4 and 5 are all worse than those of Example 1; From Example 1, Comparative Examples 6 to 7 and Comparative Examples 1 to 3, when the first sintering is cancelled and nitride is added, or the second sintering is cancelled and nitride is added, the particle size, primary particle size and compaction density are all greater than those of Comparative Examples 1 and 2, but the particle size of Comparative Example 6 is smaller than that of Comparative Example 3, and the particle size, primary particle size and compaction density of Comparative Examples 6 to 7 are all worse than those of Example 1.
[0110] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A composite positive electrode material, characterized in that: The invention comprises an outer shell layer and an inner core material, wherein the outer shell layer comprises a metal nitride; wherein the chemical formula of the inner core material is LiNi x Co y Mn 1-x-y-z Me z O2, 0≤x≤1, 0≤y≤1, 0≤z≤0.2, and x+y+z>0; the chemical formula of the metal nitride is Me p N q , 1≤p≤3, 1≤q≤3; wherein Me includes at least one of Mn, Co, Ni, Fe, Al, Cu, Ti, Cr, Zr, Zn, Mg and W.
2. A composite positive electrode material according to claim 1, characterized in that: The mass ratio of the outer shell layer and the inner core material is (0.1-0.3):
100.
3. A composite positive electrode material according to claim 1, characterized in that: The composite positive electrode material includes secondary particles composed of a plurality of primary particles, the primary particles are polycrystalline particles, and the ratio of the particle size D50 of the primary particles to the particle size D50 of the secondary particles is 1:(5-40).
4. A composite positive electrode material according to claim 3, characterized in that: The particle size D50 of the secondary particles is 8 to 40 μm; the particle size D50 of the primary particles is 0.8 to 2.0 μm.
5. A method for preparing a composite positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, after the lithium compound, the nickel-cobalt-manganese ternary precursor and the metal nitride are uniformly mixed, the first stage of sintering is performed under a protective atmosphere, and then the temperature is continuously raised to perform the second stage of sintering, and then the temperature is kept, and after cooling, the mixture is ground in an inert atmosphere to obtain a pre-sintered product; S2. Add metal nitride to the pre-sintered product, and then fully mix it, perform the first stage of sintering under a protective atmosphere, continue to increase the temperature to perform the second stage of sintering, then keep the temperature, grind it in an inert atmosphere after cooling, and finally obtain a composite positive electrode material.
6. The method for preparing a composite positive electrode material according to claim 5, characterized in that: In step S1, the molar ratio of the lithium compound, the nickel-cobalt-manganese ternary precursor, and the metal nitride is Li:(Ni+Co+Mn):Me=(1.01-1.10):1:(0.005-0.3).
7. The method for preparing a composite positive electrode material according to claim 5, characterized in that: In step S1, the first stage sintering temperature is 800-1400°C, the heating rate is 1-5°C / min, and the sintering time is 2-10h; The second stage sintering temperature is 1200-1800°C, the heating rate is 5-10°C / min, the sintering time is 1-8h, and the insulation temperature is 400-1000°C.
8. The method for preparing a composite positive electrode material according to claim 5, characterized in that: In step S2, the first stage sintering temperature is 600-1200°C, the heating rate is 1-5°C / min, and the sintering time is 4-14h; The second stage sintering temperature is 1000-1600°C, the heating rate is 5-10°C / min, the sintering time is 1-8h, and the insulation temperature is 200-800°C.
9. A positive electrode sheet, characterized in that: The composite positive electrode material comprises the composite positive electrode material according to any one of claims 1 to 4.
10. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Zirconium-containing lithium ion battery anode material and preparation method thereof and lithium ion battery
CN108807913A
Modified lithium nickel cobalt manganese oxide ternary positive electrode material and preparation method and application thereof
CN111430710A
Ternary positive electrode material, lithium ion battery positive electrode plate and application of lithium ion battery positive electrode plate
CN113921791A
Hollow ternary positive electrode material and preparation method thereof
CN115000383A
Ternary positive electrode material, preparation method and application thereof
CN116247210A